Utilization of Financial Statement Information and Planning Orientation on the Quality of Business Decisions of Textile MSMEs in West Java - Junaidi Junaidi; Lainatusshifa Kemal; Azhar Azhar; Humairoh Humairoh; Pocut Ainiah; Wahyuni Sri Astutik (West Science Accounting and Finance, 2026)
This study aims to examine the influence of financial statement information utilization and planning orientation on the quality of business decisions among textile Micro, Small, and Medium Enterprises (MSMEs) in West Java. The research adopts a quantitative approach using a survey method involving 155 MSME owners and managers as respondents. Data were collected through structured questionnaires measured on a Likert scale and analyzed using SPSS version 25. The analytical techniques employed include descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that financial statement information utilization has a positive and significant effect on decision quality, suggesting that MSMEs that effectively use financial data tend to make more accurate and informed decisions. Planning orientation also demonstrates a positive and significant influence, indicating that structured and forward-looking planning enhances the effectiveness of business decisions. Simultaneously, both variables significantly affect decision quality, with a coefficient of determination (R²) of 0.475, meaning that 47.5% of decision quality is explained by the two independent variables. This study contributes to the literature by integrating financial information utilization and planning orientation as key determinants of decision quality in MSMEs. Practically, the findings emphasize the importance of improving financial literacy and strengthening planning practices among textile MSMEs to enhance decision-making effectiveness and business sustainability.